Iklim Komunikasi Organisasi Pengawas, Kepala Sekolah, dan Guru dalam Membangun Keterbukaan di Majelis Pendidikan Muhammadiyah - Suriana Suriana; Rahmanita Ginting; Muhammad Thariq (Universitas Medan Area, 2025)
This article or paper aims to analyze the organizational communication climate between managerial supervisors, school principals, and teachers in building openness and positive behavior in the Muhammadiyah Commerce Education Council and its obstacles. This study uses a qualitative approach with the theory of communication climate, organizational communication, positive attitudes, openness, and communication barriers. The subjects are Managerial Supervisors, Principals, and Teachers in the Basic Education Council and Muhammadiyah Commerce Branch. Data was obtained through interviews, observations, and documentation from 10 informants, with data analysis through reduction, presentation, and conclusions drawn. This study concludes that the organizational communication climate in the Primary and Secondary Education Council of the Muhammadiyah Commerce Branch Executive is effective, with vertical communication between leaders, supervisors, and principals, as well as horizontal communication between teachers. Formal and informal communication processes support the creation of openness and positive behaviors such as discipline, cooperation, and innovation. Communication barriers occur due to individual psychological discomfort in communicating.